Atsar at-Ta’allum al-Qa`im ‘ala al-Maham min Khilali Tashmimi al-Mulshaq ar-Raqmi ‘ala Musyarakati ath-Thullabi fi Ta’limi Maharati al-Kitabati bi Madrasati “Pembangunan” al-Mutawassithah al-Islamiyyah - Dimyati, Sanja (Universitas Negeri Malang, 2024)
Low student engagement in learning Arabic writing skills is often overlooked, especially in traditional teaching methods that fail to actively involve students. This leads to lack of practice, low motivation, and limited student participation, which hinders their ability to master writing skills. Addressing this issue is crucial to improving instruction.This study aims to reveal the impact of Task-Based Learning through digital poster design on student engagement. Engagement aspects studied include behavioral, emotional, and cognitive dimensions. A quasi-experimental design with a quantitative approach involved 48 from the ninth grade of Pembangunan Islamic Middle School, divided into experimental (n = 24) and control (n = 24) groups. Data were collected using questionnaires based on a Likert scale and observation. The experimental group scored higher engagement (90) than the control group (77.04). The t-test yielded a t-value of 10.316 with a p-value of less than 0.001, indicating that the difference between the two groups is statistically significant. These results indicate that Task-Based Learning positively affects student engagement and contributes to innovative teaching in Arabic language and literature. غالبا ما يتم التغاضي عن انخفاض مشاركة الطلاب في تعليم مهارة الكتابة، خاصة في مناهج التعليم التقليدية التي تفشل في إشراكهم بفعالية. يؤدي ذلك إلى نقص الممارسة، وضعف الدافعية، ومحدودية مشاركة الطلاب، مما يعطل إتقانهم لمهارة الكتابة. إن معالجة هذه المشكلة أمر ضروري لتحسين جودة التعليم. تهدف هذه الدراسة إلى الكشف عن أثر التعلم القائم على المهام من خلال تصميم الملصق الرقمي على مشاركة الطلاب. شملت أبعاد المشاركة المدروسة الجوانب السلوكية والعاطفية والمعرفية. تم استخدام تصميم شبه تجريبي بمنهج كمي، حيث شملت العينة 48 طالبا من الصف التاسع بمدرسة بمبانجونان المتوسطة الإسلامية، موزعين على مجموعتين: تجريبية (عددهم = 24) وضابطة (عددهم = 24). جمعت البيانات باستخدام استبانة مبنية على مقياس ليكرت والملاحظة. أظهرت النتائج أن المجموعة التجريبية حققت درجة مشاركة أعلى (90) مقارنة بالمجموعة الضابطة (77.04). كما أظهر اختبار